A CASE FOR HARMONIZING LAWS ON MARITIME INTERCEPTIONS OF IRREGULAR MIGRANTS. Issue 4 (14th October 2014) - Klein, Natalie
Abstract Maritime interceptions continue as a fundamental dimension to external border controls against irregular migration, as seen most recently in Australia's institution of Operation Sovereign Borders in late 2013. The practice of developed States has highlighted the varied application and interpretation of four bodies of international law: the law of the sea, search and rescue obligations, refugee obligations and international human rights law. This article assesses this practice and the use of laws, highlighting the fragmentation of international law that has resulted. A proposal is presented to harmonize these laws and reconcile the divergent policy perspectives of different stakeholders.